Ethnobotanical Study of Edible Plant Communities on the Slopes of Mount Merapi and Merbabu, Indonesia - Lita Ayu Umartani; Maizer Said Nahdi (Biology, Medicine, & Natural Product Chemistry, 2021)
Ethnobotany is a study of the interaction between local people and their natural environment, especially regarding the use of plants as food and medicinal ingredients. Edible plants are a daily basic need whose existence is a necessity for the people on the slopes of Mount Merapi and Merbabu. How to use plants is transferred from generation to generation to form a culture. The research was carried out in March-May 2020 with the aim of digging local knowledge about plants used as food, including staple food, vegetables and medicines by studying the species diversity, including the benefits of plant parts, habit, how to use, process and how to obtain these species. The data were collected by using a combination of qualitative and quantitative methods with in-depth interviews through 40 respondents who were selected by purposive sampling. The results showed that the communities on the slopes of Mount Merapi and Merbabu used 74 plant species from 37 families as food sources. The favorite family is Fabaceae, followed by Zingiberaceae and Solanaceae. The most widely used habitus of plants were herbs (36.49%), followed by bush (28.38%), shrubs (18.92%) and trees (16.22%). Plant parts that are widely used are leaves (29.73%), fruit (17.57%), tubers (10.81%), seeds (9.46%), roots, rhizomes and flowers (6.76%), shoots (5.40%), stems (2.70%) and water, skin and heartwood (1.35%). The most common ways to use it are eaten raw as vegetables (29.73%), boiled (16.22%) and drink (12.16%). How to obtain it are through own cultivation (72.97%), and buying at the market (21.62%). The highest use values were Adas (Foeniculum vulgare Mill.) (0.25), chili pepper (Capsicum annum L.) (0.20), turmeric (Curcuma dosmetica loir) and water spinach (Ipomoea aquatica Forsk.) (0.17). The highest importance values were rice (Oryza sativa L.) (5.23%), and fennel (Foeniculum vulgare Mill.) (4.57%).